(untitled) (Journal of the College of Education for Women, 2019)
Abstract:Bajila regarded as descending from Anmar Ibn Nizar. Al-Masudi acceptsBajila and Khath”am as being of Nizar, and asserts that it was only out of theenmity that they were said to be from the Yemen.Al-Ya”qubi tries to harmonize this by assuming that Anmar married awomen of the Yemen and that his sons Bajila and Khath”am are thusconnected to the people of this region only through their mothers line.Bajila embraced Islam in the period of the prophet. Omar 1 forced thistribe to go to Iraq instead of Al-_Sham, and gave them the quarter of Al- Sawad. Then they prohibited from that quarter by given money as reward thatmade them against omar1.This tribe assisted the forth rightly guided caliph, Ali, in Iraq against theshames because they were the adherents of Othman besides that Othmanneglected them in spite of their efforts in Qadisiya battle.Bajila assisted any movement that was against the Umayyad caliphate.Islam managed Bajila to unite with each while they were separatedamong the other Arab tribes, which made the tribe very weak, so one of theAzd tribe managed to guide one of her branches.